PHYTOCHEMICAL SCREENING OF ROOT OF CHLOROPHYTUM BORIVILIANUM L. (SAFED MUSLI): A MEDICINAL PLANT - JYOTSANA DODKE; SHWETA SAO; PANKAJ KUMAR SAHU (International Journal of Pharma and Bio Sciences, 2013)
Chlorophytum borivilianum L. (Safed musli) plants belong to family Liliaceae contain achemicals substance in the different parts mainly the root was used for investigation. The present study is aimed at development of Physico-chemical screening and to investigate the active principle present in Chlorophytum borivilianum for four types of phytochemicals have extracted such as alkaloid, steroid, protein and carbohydrate. Among the four extracts only the Chloroform extract were precede to TLC for alkaloid separation. The solvent system selected for TLC was chloroform and methanol (15:1). The shade dried root is powdered and subjected to soxhelet extraction with petroleum ether, chloroform, 95% ethanol, and distilled water for 18hr in the order of increasing polarity of solvents.